“Love will not be idle”: Non-Doing and Action in the English Mystical Tradition - Louise Nelstrop (Entangled Religions - Interdisciplinary Journal for the Study of Religious Contact and Transfer, 2023)
This essay explores the dynamic of contemplative action, which I will refer to as ‘social mysticism’, or what from the perspective of comparative mysticism we might also want to term a form of ‘non-doing’. It focuses primarily on the medieval English mystical tradition, illustrating that two forms of action are discussion—ordinary actions and those which flow out of contemplation. It is noted that the latter constitute a detached form of action. To draw out the full ramifications of social mysticism within a Christian context a short coda is added that considers mysticism in the writings of three twentieth-century anglophone writers, all of whom were strongly influenced by medieval Christian mysticism. The essay sets out to show that focusing on the relationship between mysticism and action raises questions concerning the extent to which ineffability offers the most useful marker for Christian mysticism.